2018
DOI: 10.3389/fmicb.2018.02656
|View full text |Cite
|
Sign up to set email alerts
|

A New Role of OmpR in Acid and Osmotic Stress in Salmonella and E. coli

Abstract: Bacteria survive and respond to diverse environmental conditions and during infection inside the host by systematic regulation of stress response genes. E. coli and S. Typhimurium can undergo large changes in intracellular osmolality (up to 1.8 Osmol/kg) and can tolerate cytoplasmic acidification to at least pHi 5.6. Recent analyses of single cells challenged a long held view that bacteria respond to extracellular acid stress by rapid acidification followed by a rapid recovery. It is now appreciated that both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 51 publications
2
74
1
1
Order By: Relevance
“…Because AR2 system is responsible for survival below pH 3.0 and log phase cells with overexpression of AR2 genes are not more acid resistant 4 , the CpxRA-mediated repression of AR2 in exponentially growing cells above pH 3.0 will guarantee that AR2 system is not induced in an inappropriate situation to avoid the metabolic burden. Furthermore, the sensor kinase CpxA was proved to cross-talk with noncognate response regulator OmpR 64 , which itself is involved in the acid stress response of E. coli 65,66 . All of these data indicate that E. coli has Table 1 Putative CpxR box of fabA and fabB genes from Gram − bacteria (The genome sequences of various bacteria used in this table are under the accession numbers CP009273, NC_003197, NC_002516, NC_011283, NC_013716, CP001235, NC_004741, CP001589, evolved multiple acid response mechanisms as well as precise regulatory circuits, to target specific stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Because AR2 system is responsible for survival below pH 3.0 and log phase cells with overexpression of AR2 genes are not more acid resistant 4 , the CpxRA-mediated repression of AR2 in exponentially growing cells above pH 3.0 will guarantee that AR2 system is not induced in an inappropriate situation to avoid the metabolic burden. Furthermore, the sensor kinase CpxA was proved to cross-talk with noncognate response regulator OmpR 64 , which itself is involved in the acid stress response of E. coli 65,66 . All of these data indicate that E. coli has Table 1 Putative CpxR box of fabA and fabB genes from Gram − bacteria (The genome sequences of various bacteria used in this table are under the accession numbers CP009273, NC_003197, NC_002516, NC_011283, NC_013716, CP001235, NC_004741, CP001589, evolved multiple acid response mechanisms as well as precise regulatory circuits, to target specific stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…4). OmpR is a transcriptional regulator involved in responses to osmotic and acid stress; mutations to OmpR also contribute to antibiotic resistance by altering the expression of the OmpF major porin (32)(33)(34). A recent study showed that ompF deletions reduce the permeability of β-lactams (e.g., ampicillin and ceftriaxone) across the outer membrane, thus increasing resistance (34).…”
Section: Discussionmentioning
confidence: 99%
“…The model was based on genetic analysis of a series of mutants that indicated that (i) OmpR~P was the form that regulated the porin genes and OmpR did not play a role (4) and (ii) EnvZ controls the concentration of OmpR~P via its biochemical activities (described in Section 1.7) (57). We now appreciate that OmpR plays a surprising, non-canonical role in regulating many genes (see section 3.6 and "New View") (2,3,24). The hypothesis is outlined briefly as follows: at low osmolality, there is a low level of OmpR~P present, either due to a low activity of the EnvZ kinase or a high activity of the EnvZ phosphatase.…”
Section: Affinity Model Of Porin Gene Regulationmentioning
confidence: 99%